2004
DOI: 10.1007/s00134-004-2448-5
|View full text |Cite
|
Sign up to set email alerts
|

Post mortem examination in the intensive care unit: still useful?

Abstract: After a short ICU stay (<10 days), autopsy revealed discrepancies primarily related to the cause of death associated with diseases whose diagnosis can be difficult. Following more prolonged ICU stays (>10 days), autopsy was more likely to reveal coexisting diseases unrelated to death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
52
0
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 35 publications
4
52
0
9
Order By: Relevance
“…These unexpected findings were considered as class I in 6% and as class II in 13% of the cases. These results are comparable with our previous study [13] where the discrepancy rate was 23%. Other studies have reported major diagnostic discrepancies in 5-40% of all hospitalised patients and in 7-32% of ICU patients [7,10,11,15,31,43,46,48,50].…”
Section: Discussionsupporting
confidence: 95%
“…These unexpected findings were considered as class I in 6% and as class II in 13% of the cases. These results are comparable with our previous study [13] where the discrepancy rate was 23%. Other studies have reported major diagnostic discrepancies in 5-40% of all hospitalised patients and in 7-32% of ICU patients [7,10,11,15,31,43,46,48,50].…”
Section: Discussionsupporting
confidence: 95%
“…1,3,4,[20][21][22] Given that BMT is a relatively recent medical development, one would expect it to generate interest in explaining causes of death; however, the present study shows that autopsy rates among these patients have declined between 1990 and 2004. This decline matched the diminishing rates of autopsy in the associated teaching hospital and is incongruent with the results of Allan et al 3 who reported well-preserved rates during their 11-year study period.…”
Section: Discussionmentioning
confidence: 92%
“…When reviewing different studies comparing imaging and autopsy, scoring systems to deal with discrepancies are often very different. Systems have been devised to assess accuracy of clinical diagnoses compared with autopsy [35,36] and these have been adapted for use with PM imaging compared with autopsy [7]. However, these scoring systems and others used for imaging are often devised relating to technical performance or medical audit.…”
Section: What Are the Questions? How Do We Measure Accuracy Of The Anmentioning
confidence: 99%
“…However, these scoring systems and others used for imaging are often devised relating to technical performance or medical audit. For example a "major discrepancy" would be a failure to identify a diagnosis that could have changed medical management [36] or identifying the wrong organ system in the cause of death [15].…”
Section: What Are the Questions? How Do We Measure Accuracy Of The Anmentioning
confidence: 99%